2009
DOI: 10.1111/j.1600-048x.2009.04521.x
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐pair paternity in the socially monogamous mountain bluebird Sialia currucoides and its effect on the potential for sexual selection

Abstract: Sexual selection theory posits that ornamental traits can evolve if they provide individuals with an advantage in securing multiple mates. That male ornamentation occurs in many bird species in which males pair with a single female is therefore puzzling. It has been proposed that extra-pair mating can substantially increase the variance in reproductive success among males in monogamous species, thus increasing the potential for sexual selection. We documented the frequency of extra-pair paternity and examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…Studies reporting results inconsistent with Bateman’s principles 17 - 20 and the many studies showing a benefit of polyandry 21 - 24 for females implicitly reject Bateman’s conclusion that selection does not favor female multiple mating. The studies that demonstrated consistency with Bateman’s principles 4 , 6 , 25 - 28 piqued our interest further, as alternative explanations for Bateman’s observations besides sexual selection have also been available for at least 25 years; yet few workers have tested their observations against these alternatives 15 , 29 . A repetition could have put our minds to rest about the validity of Bateman’s conclusions and might have provided an unbiased evaluation of mate number and reproductive success that would allow robust tests of the currently obvious alternatives 15 , 29 .…”
Section: Why Did We Replicate Bateman (1948)?supporting
confidence: 52%
“…Studies reporting results inconsistent with Bateman’s principles 17 - 20 and the many studies showing a benefit of polyandry 21 - 24 for females implicitly reject Bateman’s conclusion that selection does not favor female multiple mating. The studies that demonstrated consistency with Bateman’s principles 4 , 6 , 25 - 28 piqued our interest further, as alternative explanations for Bateman’s observations besides sexual selection have also been available for at least 25 years; yet few workers have tested their observations against these alternatives 15 , 29 . A repetition could have put our minds to rest about the validity of Bateman’s conclusions and might have provided an unbiased evaluation of mate number and reproductive success that would allow robust tests of the currently obvious alternatives 15 , 29 .…”
Section: Why Did We Replicate Bateman (1948)?supporting
confidence: 52%
“…In addition, the success of older males may influence the strength of selection acting upon older age classes, with a potential impact upon reproductive senescence (Graves 2007). The lack of a negative correlation between EPP and WPP effect sizes also suggests that across species the success of older males in siring extra‐pair young does not result in paternity losses with their social mates (Balenger et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although socially monogamous, the rate of extra‐pair paternity is high in this species (72% of broods; Balenger et al. ), thus providing the opportunity for sexual selection. Because both sexes contribute to offspring provisioning and territory defense (Gibson and Moehrenschlage ), mutual mate choice is expected to be beneficial (Clutton‐Brock ).…”
mentioning
confidence: 99%
“…To date, few investigators have applied the Good Parent and Differential Allocation hypotheses to females to test whether plumage coloration is an indicator of the extent of parental care. Among studies that have been conducted, results are mixed and have revealed positive (Linville et al 1998, Jawor et al 2004, Siefferman and Hill 2005, negative (Badyaev and Hill 2002, Johnsen et al 2005, Osmond et al 2013, and no relationships (Rohde et al 1999, Smiseth and Amundsen 2000, Balenger et al 2007) between attractiveness and parental care.…”
mentioning
confidence: 99%